Standard deviations - Bender, Kara Leigh (2013)
The show Standard Deviations is composed of fifty-six relief prints based off of the combination and reorganization of two hundred and fifty linocuts. Within my work I am attempting to create a narrative space that uses a combination of object representations to form a single environment. The images produced by these composites relay narratives through image and viewer relationships. Standard Deviations deals with the altered perception, degradation, and rehabilitation of human and material components. It notes narrative and ethnographical values through image distortion, resulting in an exploration of mankind’s self-integration with objects of pseudo-natural landscapes. The depictions used within the final compositions redefine and reshape the purposes and definitions behind the original human and inanimate objects for the sake of finding meaningful mythology within the everyday. Individual images of works included.